с алгеброй, Решите уравнения: 1)4(x-3)=x+6 2)(5x+8)-(8x+14)=9 3)5\6(1\3x-1\5)=3x+3 1\3

с алгеброй, Решите уравнения: 1)4(x-3)=x+6 2)(5x+8)-(8x+14)=9 3)5\6(1\3x-1\5)=3x+3 1\3

  • 3)
     frac{5}{6} ( frac{1}{3} x- frac{1}{5} )=3x+3 frac{1}{3}
     frac{5}{18} x — frac{1}{6} = 3x + frac{10}{3}
    3x- frac{5}{18}x = -  frac{1}{6}   - frac{10}{3}
     frac{54-5}{18} x = frac{-1-20}{6}
     frac{49}{18}x = -  frac{21}{6}
    x=- frac{21}{6} :  frac{49}{18}
    x=- frac{21*18}{6*49}
    x=- frac{3*7*2*9}{3*2*7*7}
    x= frac{9}{7}
    x=1 frac{2}{7}
  • 1) 4(х-3)=х+6
    4х-12=х+6
    4х-х=6+12
    3х=18
    х=6
    Ответ: х=6
    2) (5х+8)-(8х+14)=9
    5х+8-8х-14=9
    -3х=9-8+14
    -3х=15
    х= -5
    Ответ: х= -5

Добавить комментарий

Ваш e-mail не будет опубликован. Обязательные поля помечены *